2022
DOI: 10.1002/lary.30479
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Versus Microscopic Type‐1 Tympanoplasty: A Meta‐Analysis of Randomized Trials

Abstract: Objectives Totally endoscopic ear surgery is becoming increasingly utilized in otologic practice. Although the well‐established microscope‐assisted tympanoplasty remains the most common technique to repair a tympanic membrane defect, the merits of endoscopic approaches have been well‐documented. This systematic review and meta‐analysis compares the outcomes of endoscopic to microscopic tympanoplasty incorporating only randomized trials. Study Design Systematic review and meta‐analysis. Methods A comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…This study demonstrated high rates of graft success (91%) after type 1 exoscopic and microscopic tympanoplasty at 6 months postoperatively. These rates are equal to if not better than the rates reported in the literature (5). Overall, this study demonstrates that in the hands of a capable surgeon, both exoscopic and microscopic type 1 tympanoplasty can be highly successful.…”
Section: Discussionsupporting
confidence: 63%
“…This study demonstrated high rates of graft success (91%) after type 1 exoscopic and microscopic tympanoplasty at 6 months postoperatively. These rates are equal to if not better than the rates reported in the literature (5). Overall, this study demonstrates that in the hands of a capable surgeon, both exoscopic and microscopic type 1 tympanoplasty can be highly successful.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, although mastoid obliteration has been touted as a means to minimise recurrence in children, it is clear from the current series that when using obliteration for more severe paediatric cholesteatoma, the prevention of recurrence cannot be guaranteed. Recognising that trans-canal endoscopic surgery has significantly less post-operative morbidity than post-auricular surgery [41], that use of endoscopes reduces the risk of residual cholesteatoma [42] while maintaining equivalent perforation closure rates [43], and that there is an improvement in hearing from ossiculoplasty [44], the lack of any detectable difference in recurrence rates with this approach suggests that, when possible, paediatric cholesteatoma should be removed using this approach. More extensive disease will continue to need trans-mastoid surgery with or without mastoid obliteration.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study comparing endoscopic and microscopic approach in cholesteatoma surgery confirmed that EES is safe and both the approaches have comparable results (Panetti et al, 2017). A review study suggested that limited prospective and comparative papers on MES vs EES, several aspects remain debatable (Crotty et al, 2023). This prospective study was conducted to compare MES with EES in patients with attic cholesteatoma, particularly we evaluate intraoperative characteristics and surgical outcomes of both procedures.…”
Section: Figure 1: Site Wise Distribution Of Dehiscent Tympanic Segme...mentioning
confidence: 97%